Perception of Medical Students toward Virtual Practical Sessions during COVID-19 Pandemic: A Cross-sectional Study - Samia T. Al-Shouli; Afnan Younis; Abdulaziz Alamri; Abdullah Alhumimidi; Abdulrahman Barashid; Ibraheem Altamimi; Raed Alnutaifi; Sultan Alwaily; Osman Adamu Dufailu; Khaldoon Aljerian (Wolters Kluwer Medknow Publications, 2024)
Introduction The COVID-19 pandemic disrupted the conventional mode of teaching and learning in educational institutions. To overcome the challenges, virtual delivery got tractions globally including the Kingdom of Saudi Arabia. In Saudi Arabia, the virtual delivery approach was used for practical teaching sessions in medical schools. Objectives The study assessed medical students' overall perception of virtual practical sessions. Materials and Methods A descriptive cross-sectional study was conducted between June and November 2021 at King Saud University (KSU), Kingdom of Saudi Arabia. Three hundred medical students at KSU participated in the survey with their phones using a validated Likert-based virtual questionnaire. The questionnaire was divided into three sections: the first evaluated the general perception of engagement with virtual practical sessions, the second focused on specific subject perception, and the third focused on the overall satisfaction and comfort of virtual practical sessions to students. The collected data were analyzed using the SPSS 28.0 statistical software. Categorical variables were represented using frequencies and percentages. The frequency and percentages of responses to all items on the Likert scale were detailed in the results tables. Results Of the 300 medical students who participated, 243 (81%) were eligible to be included in the study. More than half of the students (57.2%) think that virtual practical sessions cannot compensate for practical education and seminars. Fifty-eight percent of the students reported concerns of the lack of hands-on practicals for anatomy. Contrary, more than half of the students did not report concerns of the lack on hands-on in learning for practical education in histology (60.9%), radiology (56.8%), biochemistry (51.9%), and microbiology (51%). Although there were no predominant opinions regarding overall satisfaction and comfort, nearly half of the students agreed that they were overall satisfied (48.2%). Conclusion Except for anatomy, students have found virtual practical sessions to be a good replacement modality that can compensate for hands-on practical education. For students to have the practical's feel in the form of virtual reality for anatomy, highly sophisticated virtual learning technologies (platforms) have to be developed and introduced. Otherwise, the classical on-campus anatomy practical sessions should be maintained, even during difficult times such as the COVID-19 era but with adequate precautionary measures.